Trypsin inhibitor in corn (Zea mays L.) as influenced by genotype and moisture stress - Halim, A. H.; Wassom, C. E.; Mitchell, H. L. (Crop Science Society of America, 1973)
This study was undertaken to evaluate the distribution of trypsin inhibitor in kernels of genetically different strains of corn (Zea mays L.) and to determine the levels of the inhibitor in kernels as affected by water stress conditions. Crude extracts of endosperms and embryos (including scutellum) were separately analyzed for trypsin inhibitor activities.